Problematic issues of acetabular component selection with endoprosthetics of patients with dysplastic coxarthrosis (review of literature) - Loskutov, Oleg (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2018)
Dysplastic coxarthrosis is one of the major pathologies of joints in young people, which causes disability. Hip joint replacement in the case of dysplastic coxarthrosis is a complicated and intensive intervention due to anatomical deformation of the acetabulum and proximal femur, which affects the choice of the implant design, primarily acetabular component, and the method of fixing it. The main reason for the revision surgeries is the early instability of the endoprosthetic cup. Objective: to analyze the scientific information on the choice of the design of acetabular component in the case of total hip endoprosthetics in patients with dysplastic coxarthrosis. Methods: search has been conducted over the past 25 years from the PubMed, Medline, Google Scholar databases, monographs, articles, dissertations, etc. Results: in the first stages of the introduction of endoprosthesis under the conditions of dysplastic coxarthrosis, cement cups were used, which were fixed by the method of deepening of the cavity, formation of the bed and bone plastics of the zone of a segmental defect. The high level of instability of this type of cups is determined. Nowadays there are semi-spherical cups that are pressed, covered with hydroxyapatite and trabecular metal. It is noted that in case of deepening of the cup in the recipient’s bed less than 75 %, the risk of instability is very high. There is no data on the behavior of crammed cups in the conditions of segmental and central defects. To prevent the central migration of the cup into the pelvic cavity, it is proposed to use anti-rupture rings. A promising direction is the creation of cups, which are screwed and pressed, with osteoaggressive and osteoinductive coatings.